The off-modern - Boym, Svetlana 1959-2015 (New York Bloomsbury Academic, an imprint of Bloomsbury Publishing, Inc., 2017)
"The Off-Modern charts a fresh path beyond the categories of modernism and postmodernism, center and periphery, artistic theory and practice"--Provided by publisher.
Introduction (Tamar Abramov, Koc University, Turkey; Giuliana Bruno, Harvard University, USA; David Damrosch, Harvard University, USA) -- 1. History Out-of-Sync -- 2. Cultural Exaptation -- 3. Human Error -- 4. Nostalgic Technologies -- 5. Digital Resident Aliens -- 6. Edgy Geography -- 7. Archive of Pentimenti -- 8. Perspectivism -- 9. Prospective Nostalgia -- 10. Ruinophilia -- 11. Off-Modern Urbanism -- 12. Embarrassing Monumentality -- 13. Tact and Touch -- 14. Diasporic Intimacy -- 15. Immigrant Arts -- 14. Alternative Solidarities and Feminine Friendships -- 17. Estrangement for the World -- 18. Defamiliarized Human -- 19. Squiggles, Spirals, and Serpentine Dances -- 20. The Off-Modern Museum -- 21. Hypertextual Design and Essayistic Drift -- 22. On Off -- Practices -- Unforeseen Homecoming -- Phantasmagorias of History -- Turning the Page on the Avant-Garde -- Hybrid Utopias -- Global Transits and Portable Homes -- Postindustrial Art Nouveau: Tirana Arabesques 2010 -- Multitasking with Clouds -- Airport Ruins -- Hydrant Immigrants -- Not Working -- Black Mirrors -- Notes.
Includes bibliographical references (pages 183-188) and index.
Keywords: Modernism (Aesthetics); Art, Modern -- 20th century -- Philosophy; Art, Modern -- 21st century -- Philosophy